Rutin-Loaded Silver Nanoparticles With Antithrombotic Function - Wu, Haitao; Su, Manlin; Jin, Hui; Li, Xinyu; Wang, Puyu; Chen, Jingxiao; Chen, Jinghua (Frontiers in Bioengineering and Biotechnology, 2020)
In this paper, we fabricated rutin-loaded silver nanoparticles (Rutin@AgNPs) as the nano-anticoagulant with antithrombotic function. The serum stability, anticoagulation activity, and bleeding risk of Rutin@AgNPs were evaluated. The results showed Rutin@AgNPs had good serum stability, hemocompatibility, and cytocompatibility. The anticoagulation activity of rutin was maintained, and its stability and aqueous solubility were improved. The Rutin@AgNPs could provide a sustained release to prolong the half-life of rutin. The results of the coagulation parameter assay and thrombus formation test in mice model showed that the activated partial thromboplastin time and prothrombin time were prolonged, and Rutin@AgNPs inhibited the thrombosis in the 48-h period. Moreover, the limited bleeding time indicated that the Rutin@AgNPs significantly minimized the hemorrhage risk of rutin. This Rutin@AgNPs is a potential anticoagulant for antithrombotic therapy.